Veinte años de funcionamiento del Mercado Eléctrico Mayorista en Colombia: algunas reflexiones (2015)
The aim of this paper is to analyze wholesale electricity market performance in the twenty years of existence. After describing spot market operation, the market for long-term and reliability charge, we analyzed the effect of variables such as El Niño, the reservoir level, the ratio of the actual availability and market demand and some effects of regulatory changes on the spot price. Also through a stochastic model we set up some recommendations on how to improve the functioning of this market with standardized contracts implementation considering international experience. Despite the market's advance in these twenty years of operation, there are still issues to be resolved, such as contracts standardized long-term implementation, smart grids and lowering the threshold to enter the unregulated market, as these aspects would help to reduce the spot price.